Pemberdayaan PKMB Rumah Pintar Melalui Penerapan Aplikasi “ROOMPI” untuk Meningkatkan Layanan dan Literasi Bagi Masyarakat Desa Karangharjo, Kabupaten Jember - Alif Auliya, Yudha; Fadah, Isti; Baihaqi, Yustri; Arya Ranggianto, Narandha; Budi Yuswanto, Istatuk (JURNAL PENGABDIAN MASYARAKAT (JPM), 2024)
Karangharjo is a constituent village situated in the Silo District, under the Jember Regency of the East Java Province. Statistically, a significant number of individuals residing in rural regions have not attained schooling up to the junior high school or senior high school level. In 2018, the Community Learning Center (PKBM) Rumah was founded with the aim of ensuring universal access to education. Rumah Pintar provides three comprehensive services: the coordination of educational programs for packages A, B, and C, provision of basic and advanced literacy services, and establishment of community reading gardens. Two priority issues have been successfully addressed. The initial concern pertains to the administration of the PKBM Rumah Pintar services, which at present remains manual and lacks support for remote learning. The second concern regarding the human resources at Rumah Pintar is the insufficient proficiency in soft skills related to information technology. For the purpose of addressing the issue, the application "ROOMPI" has been created. The objective of this application is to enhance the effectiveness, efficiency, and accessibility of services for the general population. One approach to address the second issue is to enhance the capabilities of human resources in the areas of service management and efficient information technology management. The testing results acquired utilizing the SUS approach yielded a score of 85, which falls within the acceptable range. Furthermore, the assessment findings indicate that 83% of users express satisfaction, and the ROOMPI program greatly boosts learning motivation